The dialectics of ‘home’ in Ghassan Kanafani’s Men in the Sun - Shamallakh, Mohammed Lami S. A.; Ravichandran Vengadasamy,; Mohamed Zain Sulaiman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Since the Palestinian Nakba in 1948, the definition of home in diasporic Palestinian literature has become a central issue among literary scholars. However, this concept of home has been addressed mainly from a mono-dimensional perspective, that is, either the concrete attachment or the abstract affiliation of home. Based on the significance of the interplay of both dimensions and the lack of focus on the duality of home in previous studies of Palestinian literature, this paper explores the abstract and concrete dimensions of ‘home’ as depicted in the novel Men in the Sun written by Ghassan Kanafani, a Palestinian diasporic writer. This study investigates the paradoxes of home for Palestinians in the aftermath of the Palestinian Nakba, with a special focus on Kanafani’s perception of home. The study adopts Georg Hegel’s dialectics of thesis, antithesis and synthesis in the discussion of the abstract and concrete perceptions of home. Our findings disclose that Kanafani projects the many spaces that the refugees seek shelter in, such as the refugee camp, as the antithesis of home and that they are attached to poverty, humiliation, and death. Not only does Kanafani deny any mediating solutions for home, but he also assures us that such mediating solutions, other than the original home, will lead to additional aggravation to the original problem of displacement. Therefore, the synthesis of home, in both its concrete and abstract dimensions, remains as Palestine. It is hoped that this paper will pave the way to a better understanding of the concept of a Palestinian home.